Preconditions of Emergence and Development of Sharing Economy: Theoretical and Civilizational Approaches - ISHTIRYAKOVA, Leysan; ZAINULLINA, Milyausha (Journal of Advanced Research in Law and Economics; Vol 11 No 3 (2020): JARLE Volume XI Issue 3(49) Summer 2020, 2020)
The relevance of this research reflects the fact that the issues of consumption are as important for steady economic growth and sustainable social development as the issues of production and investment. However, there is no sufficient theoretical base on the subject for now. The purpose of this research is to describe the diverse continuum of consumption development processes across different stages of social development, which preceded and contributed to the evolution of the sharing economy in its modern form. Classical and neoclassical schools and, to some extent, institutionalism approached the category of consumption and discovered some characteristic features. Further, the evolutionary analysis of this phenomenon is addressed in conjunction with the three-stage historical civilizational concept comprising the agrarian, industrial and post-industrial stages. The major factors are identified which contribute to the development and advance of the sharing economy as a result of the evolutionary trajectory of consumption across various societal stages.